1989
DOI: 10.1073/pnas.86.6.1841
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus 1 protease expressed in Escherichia coli behaves as a dimeric aspartic protease.

Abstract: Recombinant human immunodeficiency virus 1 (HIV-1) protease, purified from a bacterial expression system, processed a recombinant form of its natural substrate, Pr55sag, into protein fragments that possess molecular weights commensurate with those of the virion gag proteins. Molecular weights of the protease obtained under denaturing and nondenaturing conditions (11,000 and 22,000, respectively) and chemical crosslinking studies were consistent with a dimeric structure for the active enzyme. The protease appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
83
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(86 citation statements)
references
References 33 publications
3
83
0
Order By: Relevance
“…The active form of the enzyme behaves as a dimer (11,12). These findings have been confirmed by the elucidation of X-ray crystallographic structures of the enzyme both unbound (13)(14)(15) and bound to synthetic inhibitors (16)(17)(18)(19)(20).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The active form of the enzyme behaves as a dimer (11,12). These findings have been confirmed by the elucidation of X-ray crystallographic structures of the enzyme both unbound (13)(14)(15) and bound to synthetic inhibitors (16)(17)(18)(19)(20).…”
supporting
confidence: 57%
“…The activity of the protease is required for viral infectivity in vitro (4). Consequently, HIV-1 PR is an attractive therapeutic target for rational drug design (5,6), and the focus of a tremendous amount of research.HIV-1 PR has been characterized as an aspartic acid protease based on sequence homology to related enzymes (7, catalytic pH studies (8), and inhibition by wellknown aspartyl protease inhibitors (9,10).The active form of the enzyme behaves as a dimer (11,12). These findings have been confirmed by the elucidation of X-ray crystallographic structures of the enzyme both unbound (13-15) and bound to synthetic inhibitors (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…However, the striking similarities in the biological effects of this group of compounds against lentiviruses and murine C-type retroviruses may not have been so predictable. Overall, HIV and the MuLVs display limited sequence homology except for two highly conserved domains, one of which encompasses the protease enzyme's active site (12,16,20). In the proteases of these viruses, as in all known retroviral proteases, the active site includes the prototypic Asp-Thr-Gly sequence, from which the aspartic proteases derive their name (12,16,20).…”
Section: Resultsmentioning
confidence: 99%
“…Retroviral proteases, which form homodimers in the ac-tive state (20,23,25,26,35), belong to the class of aspartic proteases, all of which contain a pair of highly conserved regions composed of two hydrophobic amino acids followed by the characteristic sequence Asp-Thr/Ser-Gly (12,16,20).…”
mentioning
confidence: 99%
“…Miller et al (1989a) reported a structure for the proteinase of Rous sarcoma virus (RSV); both Navia et al (1989) and Lapatto et al (1989) reported structures for HIV-1 proteinase; and Wlodawer et al (1989) reported a structure for a synthetic HIV-1 proteinase (in which the cysteine residues were replaced by c~-amino-n-butyrate). The material for these analyses was obtained by three methods: the RSV enzyme was extracted from virions; Navia et al and Lapatto et al utilized Various, studies, including the crystallographic analyses, indicate that the active form of the proteinase is a dimer (see also, for instance, Meek et al, 1989). As had previously been proposed, the retroviral proteinases can be seen from their folding pattern to belong to the family of aspartic proteases, such as pepsin; these are so called because their active site contains two essential aspartate residues, each in the characteristic sequence Asp-Thr(or Ser)-Gly.…”
Section: Retroviral Proteinasesmentioning
confidence: 99%